Pelatihan Manajemen Risiko Bagi Pelaku Usaha Mikro, Kecil dan Menengah Bagi Warga Belajar Pendidikan Kesetaraan Paket C di PKBM Cerdas Mandiri Kecamatan Peureulak - Jamali; Muhammad Jamil; Ismail; T. Muana Refi; Abdul Aziz; Cut Evawani; Esti Alemia Puspita; Vizatul Ola (Yayasan Kawanad, 2022)
This activity aims to provide risk management training for Micro, Small and Medium Enterprises for Community Learning Equivalent Education Paket C at PKBM Cerdas Mandiri, Peureulak District in order to increase knowledge, apply in dealing with risks that arise in building Micro, Small and Medium Enterprises for residents. learn Equivalence Education Package C who are members of the PKBM Cerdas Mandiri. The location of community service activities is carried out through face-to-face meetings at the PKBM Cerdas Mandiri Peureulak. Community Service Activities use the Pre-Test and Post-test methods, providing material by mentors, presentations by participants, and discussion and product exposure. The results of the activity provide knowledge for participants while still paying attention to the development of the business world and technological developments as well as insurance in running a business, by being able to predict the risks that will occur from the start, both financial data, place of business and external influences that cannot be predicted or the emergence of a business that is unpredictable. In the same way, it will be able to minimize the risk of losses that occur to UMKM carried out by Equality Education Participants in Peureulak District, East Aceh Regency